1999
DOI: 10.1073/pnas.96.26.15268
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neurotransmission in mice lacking synaptic vesicle protein 2A (SV2A)

Abstract: Synaptic vesicle protein 2 (SV2) is a membrane glycoprotein common to all synaptic and endocrine vesicles. Unlike many proteins involved in synaptic exocytosis, SV2 has no homolog in yeast, indicating that it performs a function unique to secretion in higher eukaryotes. Although the structure and protein interactions of SV2 suggest multiple possible functions, its role in synaptic events remains unknown. To explore the function of SV2 in an in vivo context, we generated mice that do not express the primary SV2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
344
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(378 citation statements)
references
References 33 publications
24
344
1
2
Order By: Relevance
“…Treatment with the miR-M or miR-I did not affect the number of presynaptic terminals (SYP38 + puncta). The finding that miR-485 regulated the expression of SV2A, a ubiquitous presynaptic protein that regulates neurotransmitter release (26), suggested that synapses may be altered structurally as a consequence of changes in synaptic function. We therefore tested the function of miR-485 on several morphological properties of hippocampal synapses.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with the miR-M or miR-I did not affect the number of presynaptic terminals (SYP38 + puncta). The finding that miR-485 regulated the expression of SV2A, a ubiquitous presynaptic protein that regulates neurotransmitter release (26), suggested that synapses may be altered structurally as a consequence of changes in synaptic function. We therefore tested the function of miR-485 on several morphological properties of hippocampal synapses.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that the proteins interact with synaptotagmin 1 367 to cause an enhancement of low-frequency neurotransmission by priming docked vesicles. 368 Specificially, SV2 is believed to prime vesicles in quiescent neurons so that low-frequency neurotransmission is faithfully conveyed. 369 The AED levetiracetam and its analogs brivaracetam and seletracetam bind specifically to SV2A and not to the other SV2 proteins.…”
Section: Synaptic Vesicle Proteinsmentioning
confidence: 99%
“…10 SV2A is not essential for synaptic transmission, but knockout of the protein in mice leads to severe seizures (in constrast to SV2B knockout mice, which do not show seizures). 367,368 The way in which binding of levetiracetam and related compounds to SV2A influences seizure susceptibility is not understood. However, the identification of SV2A as an AED target demonstrates the potential of targeting proteins other than ion channels for AED development.…”
Section: Synaptic Vesicle Proteinsmentioning
confidence: 99%
“…Particular attention has been given to synaptic vesicle protein 2A, a membrane glycoprotein present in synaptic vesicles of neurons and a calcium regulator in neurotransmitter release [46], as it is the binding site for the antiepileptic, levetiracetam [47]. It has been shown to have a low distribution in the cerebral cortex and hippocampus of spontaneously epileptic rats [48] and its removal in knockout mice promotes severe seizure development [49]. Expression of SV2A in human peritumoural cortex in both low-and highgrade gliomas, however, was no different between those patients identified with epilepsy and those without, suggesting different mechanisms of regulation of SV2A than in the models examined (50).…”
Section: Neurobiologymentioning
confidence: 99%